Knowledge-based economy as a foundation for the economic development of countries - Santos López Leyva; Ana Bárbara Mungaray-Moctezuma (Management dynamics in the knowledge economy, 2017)
This paper highlights the relationship between knowledge and economic development. The study considers nine countries grouped in three different development models: 1) the Asian model includes Japan, the Republic of Korea, and Singapore; 2) the Anglo-Saxon model includes the United Kingdom, the United States, and Canada and 3) the European model includes Germany, France, and the Netherlands. The data was sourced from the Global Competitiveness Report of the World Economic Forum, the PISA reports, the Academic Ranking of World Universities (ARWU) and the Global Innovation Index of the World Bank. The Asian group ranked highest for innovation as shown through the application of patents; they also obtained the highest scores in the PISA test. The Anglo-Saxon group stood out by having a good institutionalized knowledge system. From the European group, Germany is recognized by its innovation capabilities and the Netherlands by the quality of its higher education.
10.25019/MDKE/5.4.02; 10.25019/MDKE/5.4.02; 2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920